Parasitoides himenópteros presentes en especies ambrosiales y descortezadores recolectados de Persea americana Mill. (Laurales: Lauraceae), en Nayarit, México - Jacobo-Macías, Eric Roberto; Robles-Bermúdez, Agustín; Cambero-Campos, Octavio Jhonathan; Coronado-Blanco, Juana María; Isiordia-Aquino, Néstor; Ruíz-Cancino, Enrique; Robles-Navarrete, Alan Paul (Instituto de Ecología, A.C., 2022)
In recent years, ambrosial beetles (Curculionidae: Scolytinae) have gained relevance due to the threat posed to the avocado crop by the species Xyleborus glabratus and its symbiont agent Raffaelea lauricola (Ophiostomatales: Ophiostomataceae), as well as the Euwallacea fornicatus species complex and its associated pathogen Fusarium euwallaceae (Hypocreales: Nectriaceae), species regulated for Mexico. Within the E. fornicatus complex is Euwallacea kuroshio, a species that in 2016 was reported from Tijuana, Baja California. Therefore, it is important to know the diversity of these borers that have the potential to affect different plant hosts, including avocado. In addition, if R. lauricola and F. euwallaceae are present, native species could be secondary vectors and hosts of natural enemies. The objective of this study was to determine the parasitoids associated with native ambrosial and bark beetle species of Persea americana of Hass, Booth 8 and Choquette cultivars in the municipalities of Xalisco, Tepic and San Blas, Nayarit. The method used was the collection of plant material from different avocado cultivars infested by the attack of ambrosial species, which was introduced in modified 20-liter buckets to obtain the beetles. The hymenopteran parasitoids obtained belong to the families Braconidae, Eupelmidae and Figitidae, which emerged from branches infested mainly by Xyleborus palatus, Pityophthorus sp. and Xyleborus affinis. It is concluded that there are species of different families and genera of Hymenoptera: Parasitica that regulate populations of ambrosial scolytines and bark strippers in Nayarit.